Use of the pediatric symptom checklist to screen for behaviour problems in children - Muppidathi, Subbiah; Boj, Jenitha; Kunjithapatham, Muthukumar (International Journal of Contemporary Pediatrics, 2017)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Behavioral and emotional problems comprising internalizing, externalizing and mixed disorders consist of psychiatric disorders in childhood and adolescents. This study aimed to measure the prevalence of emotional and behavioral disorders and to evaluate the usefulness of the pediatric symptom checklist (PSC) in identifying behavioral problems in children between ages of 4 and 12 attending OPD. Methods: Parents of 450 children between the ages of 4 and 12 attending pediatric OPD were randomly selected for the study after their valid informed consent, regarding awareness of psychosocial problems in their child with the help of 17-item pediatric symptom checklist (PSC) Results: Overall, 81(18%) children had at least 1 positive PSC-17 subscale or a positive PSC-17 total score. 27 (6%) children scored positive on the internalizing subscale, 36 (8%) scored positive on the externalizing subscale, and 36 (8%) scored positive on the attention subscale. Boys had higher PSC scores than girls for both school-aged (21% vs 16%) and preschool-aged children (15%vs 9%). Children from low socio economic status (20%), living with single parent (53%), nuclear family (21%), alcoholic father (28%) and single child (33%) are the risk factors associated with increased behavioral problems. Internalizing problems were seen more commonly in older children (10 - 12years), whereas attention and externalizing problems were more commonly seen in younger children (4 - 8 years). Conclusions: This study showed the extent of childhood emotional and behavioral problems. Use of the PSC offers an approach to the recognition of psychosocial dysfunction that is sufficiently consistent across groups and locales to become part of comprehensive pediatric care in virtually all out-patient settings. Further research is needed to identify effective strategies for using primary care for recognizing, diagnosing, and treating mental health disorders in children and adolescents. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>